Revealing complexity: segmentation of hippocampal subfields in adolescents with major depressive disorder reveals specific links to cognitive dysfunctions - Yixin Zhang; Xuan Liu; Ying Yang; Yihao Zhang; Qiang He; Feiyu Xu; Xinjuan Jin; Junqi Gao; Yuan Yao; Dexin Yu; Bernhard Hommel; Xingxing Zhu; et al. (European Psychiatry)
Abstract